Gamma Interferon Is Not Required for Arthritis Resistance in the Murine Lyme Disease Model - Glickstein, Lisa (American Society for Microbiology, 2001)
Lyme arthritis is the most common complication following infection of human individuals with Borrelia burgdorferi sensu stricto. In mice, B. burgdorferi infection leads to arthritis of the tibiotarsal joints. Arthritis severity in mice is under host genetic control, as BALB/c mice developed mild arthritis but C3H/He mice developed severe disease following B. burgdorferi infection. To study the role of gamma interferon (IFN-γ) in arthritogenesis, targeted mutant mice lacking the IFN-γ receptor (IFN-γR) were infected by inoculation with B. burgdorferi. IFN-γR(−/−) and parental 129/SvEv mice developed mild arthritis of similar severity, as determined both by weekly tibiotarsal joint measurements and histopathology at 2 and 5 weeks postinfection. Both strains of mice had the same spirochetal burden in the joints, suggesting that the IFN-γR(−/−) mice were not impaired in controlling spirochetal expansion in vivo. The wild-type mice mounted a Th1 response, with a predominance of CD4(+) IFN-γ(+) T cells observed by flow cytometry. In contrast, the IFN-γR(−/−) mice mounted a Th2 response, with a predominance of CD4(+) IL-4(+) T cells. As expected given their cytokine profile, the IFN-γR(−/−) mice produced fewer CD8(+) IFN-γ(+) and MAC-1(+) IL-12(+) cells and less immunoglobulin G2a (IgG2a) than their wild-type counterparts. These results strongly suggest that IFN-γ is not required for arthritis resistance or as part of an effective immune response against B. burgdorferi.